L-R asymmetries and signals for new bosons - Montero, J. C.; Pleitez, V; Rodriguez, M. C. (American Institute of Physics (AIP), 1999)
Several left-right parity violating asymmetries in lepton-lepton scattering in fixed target and collider experiments are considered as signals for doubly charged vector bosons (bileptons).